Immunohistochemical localization of eight phospholipase C isozymes in pancreatic islets of the mouse - Kim, SS; Jun, K; Jeong, MJ; Ryu, SH; Suh, PG; Shin, HS (생화학분자생물학회, 2001)
The possible involvement of phospholipase C (PI-C) in the regulation of insulin secretion is not clearly understood and neither its isozymes expressed nor cellular localization in the pancreatic islets is known. By using specific monoclonal antibodies, we have, investigated the expression and localization of eight different PLC isozymes, beta1, beta2, beta3, beta4, gamma1, gamma2, delta1, and gamma2, in the pancreatic islets of adult mice.. immunohistochemical analysis carried out on paraffin embedded sections showed a distinct pattern of expression for each of the PLO isozymes. In the central part of the islets containing P cells, a high level of beta4 and moderate levels of beta3 and gamma1 were expressed, whereas PLC-beta1 and -gamma1 were abundantly expressed in the exocrine pancreas. These results demonstrated the heterogeneity in expression of the phospholipase C isozymes in pancreatic islets. It is conceivable that these isozymes are coupled to different receptors and perform selective tasks in the regulation of insulin secretion for glucose homeostasis.